Examining the Erosion Resistance of Cement-Bentonite Barriers: Effects of Confining Pressure and GGBS Content - Walenna, Muhammad A.; Royal, Alexander; Jefferson, Ian; Ghataora, Gurmel; Harianto, Tri; Arsyad, Ardy; Hanami, Zarah A. (Civil Engineering Journal, 2025)
This study investigates the erosion resistance of cement-bentonite (CB) barriers, focusing on the role of varying levels of Ground Granulated Blast Furnace Slag (GGBS) content and confining pressure, crucial for infrastructure such as dams and levees. Employing a bespoke modified triaxial erosion testing setup, the research assesses how different confining pressures, GGBS proportions, and curing periods impact the erosion resistance of CB materials under varying stress conditions. Results demonstrate that increasing GGBS proportions enhances erosion resistance by improving the CB matrix microstructure, while higher confining pressures generally increase resistance. However, combinations of high confining pressure and erosive force can lead to barrier material failure, with buckling failure occurring at elevated pressures (100 kPa and above), highlighting a trade-off between enhancing erosion resistance and maintaining structural stability. Extended curing periods allow for material strength development, enhancing stability, yet delayed erosion phases at higher confining pressures and longer curing durations suggest gradual crack formation, potentially leading to hydraulic fracturing. This underscores the need for meticulous design considerations regarding load conditions due to significant failure modes such as buckling. The findings emphasize that the strategic combination of GGBS content, confining pressure, and curing period is crucial in optimizing barrier performance, highlighting the importance of selecting optimal material formulations and operational parameters to maximize erosion resistance and ensure the longevity and safety of civil engineering structures.